Migración y cambios socioeconómicos en la comunidad de Zoogocho, Oaxaca - Ramos Pioquinto, Donato (El Colegio de México A.C., 1991)
Migration, as part of social reality, is a historically determined multidimensional process in which physical and natural, socioeconomic, cultural, and psychosocial factors are interrelated. Each one of the specific areas where it occurs is linked to a context which fades into a geographic and temporal immensity. Thus, to understand this phenomenon, various levels of analysis of both the internal and external factors which are involved must be established, following an order of priorities that changes according to concrete situations.This study of migration and the socioeconomic dynamics of the community of Zoogocho in the state of Oaxaca is an example of what happens in rural areas when Indian-campesinos establish contacts with foreign parts. The penetration of alien socioeconomic and cultural values alters both family and communal structures to such an extent that available resources prove insufficient in competing with the colliding external society. This leads to increasingly more complex movements of the population, the manifestations, causes and consequences of which vary through time not only in the places of origin but also in destinations. Therefore, the different characteristics which this process assumes do not let us conclude that it is the same in Zoogocho and other communities.